The Effect of Infrastructure, Investment, and Economic Growth on Community Welfare Through Employment Opportunities in Indonesia - Ayu Eliana; Endang Endang (Trunojoyo University of Madura, 2023)
Employment opportunities and community welfare are related, the opportunity for people who work will earn income for the community to fulfill their daily needs which is described by community welfare. This study used secondary data obtained through the Central Bureau of Statistics, then analyzed using path analysis techniques with the help of Eviews 12. The results showed that infrastructure and investment had a negative and insignificant effect on employment opportunities, but economic growth had a significant negative effect on employment opportunities. Infrastructure and investment have a positive and insignificant effect on the welfare of the community, economic growth has a negative effect and does not have a significant effect on the welfare of the community. Opportunity to work has a positive and significant impact on the welfare of maisyairaikait. Infrastructure has no other direct effect on the welfare of the people, while investment and economic growth can have an indirect effect on the people's welfare through the opportunity to work in Indonesia.